2021
DOI: 10.3390/genes12101499
|View full text |Cite
|
Sign up to set email alerts
|

CKM Gene rs8111989 Polymorphism and Power Athlete Status

Abstract: Multiple genetic variants are known to influence athletic performance. These include polymorphisms of the muscle-specific creatine kinase (CKM) gene, which have been associated with endurance and/or power phenotypes. However, independent replication is required to support those findings. The aim of the present study was to determine whether the CKM (rs8111989, c.*800A>G) polymorphism is associated with power athlete status in professional Russian and Lithuanian competitors. Genomic DNA was collected from 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This is because creatine kinase catalyses the conversion of phosphocreatine and adenosine diphosphate into creatine and ATP, respectively. Therefore, the efficiency of ATP generation during muscle contraction is affected by the activity of creatine kinase, particularly during short-duration, maximal-intensity exercise activities where both ATP and phosphocreatine are the main sources of energy [3]. In fact, the activity of creatine kinase in catalysing the resynthesis of ATP is two-fold in fast twitch muscle fibres compared to slow twitch muscle fibres [4], which indicates that the activity of this protein is one of the characteristics of fast muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…This is because creatine kinase catalyses the conversion of phosphocreatine and adenosine diphosphate into creatine and ATP, respectively. Therefore, the efficiency of ATP generation during muscle contraction is affected by the activity of creatine kinase, particularly during short-duration, maximal-intensity exercise activities where both ATP and phosphocreatine are the main sources of energy [3]. In fact, the activity of creatine kinase in catalysing the resynthesis of ATP is two-fold in fast twitch muscle fibres compared to slow twitch muscle fibres [4], which indicates that the activity of this protein is one of the characteristics of fast muscle fibres.…”
Section: Introductionmentioning
confidence: 99%
“…The confirmed up-regulated expression of CKM, MME, and MPO and down-regulated expression of ALDH1A2, CHGB, and SUGP1 by western blot indicated that our proteomics data were dependable. CKM was a catalytic activity protein that can reversibly catalyze various phosphogens between ATP and ADP, thereby playing an important role in maintaining the cellular energy homeostasis [ 51 ]. Moreover, Xiong et al [ 52 ] reported that CKM was highly expressed in skeletal muscle and myocardium, and its gene expression was increased after muscle cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for mountain ultramarathon athletes, these polymorphisms might manifest unique genotypic distributions, playing a pivotal role in adaptations and athletic performance. This is exemplified by studies covering power-oriented athletes [ 22 ], climbers [ 23 ], marathon runners [ 24 ], and ultramarathon runners [ 25 ].…”
Section: Introductionmentioning
confidence: 99%